Investigation of Antibiotic Resistance Genes in E. coli Isolates from Patients in Iraq - Afnan Yarob Yousif; Zahraa Abdulmunim Sharba; Sabah Saad Abdulsahib (International Journal of Medical Toxicology and Legal Medicine, 2024)
Urinary tract infections (UTIs) are among the most prevalent bacterial infections worldwide, with Escherichia coli (E. coli) being the primary causative agent. The emergence of antibiotic resistance in E. coli has become a critical global health challenge, necessitating in-depth investigations into resistance mechanisms and patterns, particularly in regions with increasing AMR prevalence. Aim: This study aimed to investigate the prevalence of E. coli, its molecular characteristics, and antibiotic resistance patterns in urinary tract infections in Iraq. A particular focus was given to identifying resistance genes (tetA and qnr) and their correlation with antibiotic susceptibility. Methods: A total of 125 urine samples were collected, of which 100 contained bacterial isolates. Conventional culturing and biochemical tests identified five bacterial species, with E. coli being the most predominant. Molecular identification using the 16S rRNA gene confirmed E. coli in 40 isolates. PCR analysis targeted the tetA (tetracycline resistance) and qnr (fluoroquinolone resistance) genes. Antibiotic susceptibility testing was conducted using the disk diffusion method on Mueller-Hinton agar, and statistical analysis was applied to evaluate demographic and resistance patterns. Results and Discussion: The study identified E. coli as the predominant pathogen, comprising 80% of the bacterial isolates. Molecular analysis revealed the tetA gene in 85% of the 40 E. coli isolates, suggesting widespread exposure to tetracycline. Additionally, the qnr gene was detected in 75% of these isolates, indicating significant resistance to fluoroquinolones. Moderate resistance rates were observed for ciprofloxacin (25%) and levofloxacin (50%), likely influenced by alternative resistance mechanisms such as efflux pumps or mutations rather than solely qnr presence. Further analysis highlighted a correlation between age and UTI incidence, with the highest rates observed in patients over 50 years. These findings underscore the pressing need for targeted antimicrobial interventions, particularly in older populations.In conclusion, the study emphasizes the critical importance of implementing effective antimicrobial stewardship programs to curb the spread of tetracycline and fluoroquinolone resistance in E. coli. Integrating molecular diagnostics into routine clinical practice is pivotal for improving UTI management and combating the global challenge of antibiotic resistance.